Análise das relações entre pressão e gestão ambiental em empresas brasileiras - Castro Neto, Francisco César de (2011)
Studies on environmental sustainability perform a recent and important agenda for management research in Brazil and worldwide in the current century. The management science within this context has fit itself to the modern sustainability and ecological concern demands by developing the environmental management as a study subarea. Environmental proactivity, an emergent topic of environmental management, considers the management action with respect to environmental self regulation developed by companies as answer for the surroundings stakeholders pressure in order to minimize the environmental impact caused by the course of its operations, nevertheless advancing in actions which go beyond the legal requirements. Immersed in this theme, this research was developed in a quantitative perspective aiming at assessing the relationships among environmental proactivity determinant factors, environmental pressure and environmental proactivity indicators. Econometric models application allowed to conclude that company size, capital internationalization and, in a less extent, position in the value chain are related to the environmental pressure exerted by stakeholders. In the other hand, such a environmental pressure performs a genuine effect on environmental proactivity actions of the companies by explaining even 25% of its behavior. Additionally, features like company size, capital internationalization and industrial sector have also proven positively related to environmental proactivity actions taken by Brazilian companies.